The Conduct of War : A Short Treatise on its Most Important Branches and Guiding Rules - Goltz, Colmar, Freiherr Von Der; Edited by James, Walter H.; Translated by Roy, G. F. Leverson, P.S.C. (Rawalpindi, Pakistan Army Education Press, 2000)
This book is a treatise on the guiding rules of war according to Lt. General Colmar von der Goltz of the Prussian Army.
Keywords: Military art and science -- War